Influence of B16/F10 melanoma growth variant on calcium levels in mitochondria in various organs of female mice - O. I. Kit; E. M. Frantsiyants; I. V. Neskubina; E. I. Surikova; I. V. Kaplieva; V. A. Bandovkina (Исследования и практика в медицине)
Purpose of the study. To analyze the calcium levels in mitochondria of cells in different organs in standard and stimulated growth of experimental В16/F10 melanoma. Materials and Methods. The study included female С57ВL/6 mice (n=168). Experimental groups: intact group (n=21), group with a model of chronic neurogenic pain (CNP) (n=21), group M – B16/F10 melanoma (n=63), group M+CNP – mice (n=63) with transplantation of B16/F10 melanoma 3 weeks after CNP model creation. The concentration of calcium in mitochondrial samples was determined by a biochemical method (Abris+, Russia). Results were statistically analyzed using the Statistica 10.0 program. Results. CNP decreased calcium levels in mitochondria of cells in the brain by 1.4 (р=0.00153) times, liver by 2.6 times and heart by 3.2 times and increased the levels in the skin by 97.1 times. In standard growth of experimental melanoma, levels of calcium in cell mitochondria in most of the studied organs increased at the initial stage of the melanoma growth, and decreased to intact values and lower by the terminal stage. In the mitochondria of tumor cells, calcium levels were stably high at all stages of standard tumor growth. At the initial stage of CNP‑stimulated tumor growth, a decrease in calcium in the mitochondria of the skin by 5.7 times and its accumulation in the mitochondria of the brain by 6.6 times, heart, and kidneys were recorded by 1.5 times. At the terminal stage of stimulated melanoma growth, extremely low calcium values were recorded in the mitochondria of all organs. A stably low level of calcium was registered in the mitochondria of tumor cells at all stages of stimulated melanoma growth. Conclusions. The growth of experimental B16/F10 melanoma in female mice is accompanied by mitochondrial dysfunction affecting most organs. Stimulation of the growth of experimental melanoma with chronic neurogenic pain, unlike the standard growth variant, changes accumulation of calcium in the mitochondria of cells both in organs and in the tumor itself. The chronic pain syndrome accompanying a malignant process can influence its course with the involvement of mitochondria and the modification of their functions.